Navigating the Liminal Space: Trauma, Transition, and Connection in Bereaved Carers' Experiences of Specialist Palliative Care in Western Sydney. Issue 2 (3rd July 2018) - Bindley, Kristin; May, Anne; Pavlek, Wendy; Coller, Suzanne; Kalkandis, Pam; Dalgleish, Trish
Abstract: Caregiving at the end-of-life has been associated with a range of physical, spiritual, social, and psychological outcomes, and influenced by encounters with providers of specialist palliative care. The purpose of this qualitative study was to explore experiences of bereaved carers of people with a life-limiting illness, in the context of care provided through a Western Sydney supportive and palliative care service. Thirteen bereaved caregivers participated in semi-structured, in-depth interviews. Transcripts were analyzed using a thematic approach, informed by thematic networks. Four domains appeared to mediate carer experiences: confrontations with trauma, suffering, and death; navigating transitions and boundaries and the caregiving role as liminal space; encountering connection in formal care contexts; and negotiating system issues. This study is one of the first to explore caregiver experiences within a low socioeconomic population in Western Sydney and provides a nuanced understanding of factors which may shape experiences of palliative care. Findings suggest that ongoing attention to the cultivation of skilful practitioners is warranted; able to companion caregivers in a manner attuned to the potential for trauma in the context of expected death. Additionally, findings call for investment in specialist sites of care alongside greater attention to public health approaches to palliative care.